Emotional Engagement Index: A Novel Tool to Measure Emotional Engagement in Blended Learning - Aziman, Abdullah; Asar, Abdul Karim; Nur Alnisa’ Anis Alanna, Ruzelan (Universiti Malaysia Sarawak (UNIMAS), 2019)
Emotional engagement is one of the core elements for implementing impactful learning experience in education as well as professional training. This element however is often been reported through self-administered questionnaire or psychometric approach. That approach may not capable to represent the context of student’s emotion in each session of the class. As a result, there is lack of indicator that measure this affective domain in consistent, simple and systematic manner. This study proposed a simple online attendance that include emotional icon or emoji as a graphical clue for students to indicate their feelings in the class during attendance signing process. The population or number of students in this study is 45. Student emotion data from each attended face-to-face session has been analyzed in formulating an emotional engagement index for each student in class. The index is a ration value from the frequency of the emotion against total class session in a semester. Based on the index, this study adopts a simple linear regression method and found that there is a positive relationship between emotion and the attainment of course learning outcomes with r =0.4557 for the cognitive domain. The proposed emotional index formulated based on emoji data is a novel approach for educators to measure student emotional engagement in blended learning environment.